Multinationals, environment and global competition - Lundan, Sarianna M. (Emerald, 2003)
The purpose of this book is to present leading research concerning the increasing strategic importance of environmental concerns within the multinational firm, and to explore the implications of corporate environmental strategy on public policy. The contributions present empirical research that deals with the simultaneous effects of the globalization of markets and the emergence of environmental concerns as issues of corporate strategy, either using a cross-national sample of firms within a global industry, or a sample of multinationals from a particular home country. By considering the dynamics of corporate environmental behavior explicitly within the context of global markets, the book makes a unique contribution to the discussion about the impact of multinational activity. The chapters provide a rich understanding of the kinds of interactions that occur between multinationals and regulators, multinationals and non-governmental organizations, and multinationals and their customers. By explaining what motivates multinational firms to make environmental investments and to improve their environmental performance, these studies offer necessary input for the formulation of well-informed public policy. As a consequence, this book provides essential material for advanced students and decision-makers interested in the changing role of multinational enterprises in the global economy. While being of broad interest to academics in the field of international business and strategy, this volume also provides interesting results to researchers concerned with the ability of national governments to regulate multinationals, how regulation affects multinationals, and how in turn multinational conduct affects regulatory standards.
Includes index.
Keywords: Business & Economics -- Management.; Business & Economics -- Economics -- General.; Multinationals.; Globalization.; International business enterprises -- Environmental aspects.; elektronické knihy; electronic books